A Multimodal and Critical Discourse Analysis of Gender Representation in an Indonesian Grade 4 Science Textbook - Barli Kifli; Isli Iriani Indiah Pane; Muhammad Aswin Rangkuti (PAROLE: Journal of Linguistics and Education, 2025)
Textbooks play a central role in shaping learners’ perceptions of social roles, including those related to gender in science education. This study investigates how gender is visually and discursively represented in the Ilmu Pengetahuan Alam dan Sosial (IPAS) Grade 4 textbook issued by the Indonesian Ministry of Education. Using a qualitative content analysis approach, the research integrates Multimodal Discourse Analysis (MDA) and Critical Discourse Analysis (CDA) to examine 44 illustrations from the natural science chapters. The analysis focuses on how agency, authority, and scientific roles are distributed across male and female characters in both visual (e.g., posture, salience) and verbal (e.g., speech functions, cognitive authority) modes. The findings indicate that male characters are more frequently depicted and are often positioned in dominant scientific roles, while female characters appear less frequently and are generally portrayed as passive, supportive, or non-expert. Although a few scenes offer inclusive representations, these are limited and do not significantly alter the prevailing gender asymmetry. The study concludes that despite policy emphasis on equity, the textbook continues to reflect traditional gender norms, particularly in STEM-related contexts. It highlights the need for intentional alignment between visual and verbal elements to support inclusive and equitable science education.